A Robust and Scalable Continuous Flow Process for Glycerol Carbonate. Issue 10 (4th September 2018) - Van Mileghem, Seger; De Borggraeve, Wim M.; Baxendale, Ian R.
Abstract: With glycerol being a bulk waste product, the interest in converting it to other value‐added products is steadily increasing. A scalable continuous flow process was developed for the synthesis of glycerol carbonate (2‐GLC) from glycerol and dimethyl carbonate on a hydroxide functional resin. High conversion and selectivity were obtained while the residence times were typically shorter than 10 min. Continuous production of 2‐GLC was achieved in high throughput and with improved processing metrics, creating the foundations for a production level process. Abstract : A robust continuous flow procedure is reported for the synthesis of glycerol carbonate from the green reagents glycerol and dimethyl carbonate, mediated by an inexpensive polymer‐supported base catalyst using methanol as co‐solvent. High conversion and selectivity were obtained with short residence times.